Successful management of severe coronoid process hyperplasia in a patient with mucopolysaccharidosis VI: a case report. Issue 1 (13th January 2020) - Khadembaschi, Darius; Arvier, John; Beech, Nicholas; Dolan, David; McGill, Jim
Abstract: Mucopolysaccharidoses are a group of rare lysosomal storage diseases caused by a deficiency of enzymes, which breakdown glycosaminoglycans, with consequent dysfunction of affected tissues. Mandibular coronoid hyperplasia, with associated trismus, has been recently described as a feature of the craniofacial abnormalities seen in these patients. However, the details of the surgical and post-operative management of these patients have not been previously documented. This case describes the successful management of severe trismus from coronoid process hyperplasia in a 14-year-old male, utilising an extra-oral approach for bilateral coronoidectomies and removal of exophytic zygomatic bone, followed by immediate and long-term physiotherapy. An improvement of mandibular opening from 8 to 45 mm has been maintained at 18 months post operation.